Permainan Ular Tangga Sebagai Media Meningkatkan Kemampuan Berhitung Anak Sekolah Dasar - Susetyawati, M.M. Endang; Wicaksono, Bintang; Oktavia, Lisa; Maharani Putri, Nadia (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
The ability to count is part of mathematics which can develop children's cognitive abilities. It is very important to develop the ability to count in children, because counting can be used in children's daily lives. The problem faced by children in their ability to count is that children lack skills in doing calculations. Lack of numeracy skills can cause low mathematics learning achievement. This research aims to examine the snakes and ladders game as a medium to help elementary school children improve their numeracy skills to solve math problems. The method used in this research is descriptive qualitative with data collection through observation, interviews and documentation. It was tested in three stages and involved nine children who had different numeracy abilities. The results of this research are that children become more skilled at doing calculations, learning becomes fun, learning activities become interactive, and motivation to learn to count increases. The snakes and ladders learning media can increase motivation to learn to count and solve math problems. Keywords: Snakes and Ladders Game, Numeracy Skills, Media